2013
DOI: 10.2478/acas-2013-0021
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic amines in red wine: The impact of technological processing of grape and wine / BIOGENI AMINI V RDEČEM VINU: VPLIV TEHNOLOŠKE PREDELAVE GROZDJA IN VINA

Abstract: The knowledge of the biogenic amines present in wine is important to consumers in terms of their potential threats of toxicity to human and to wine producers as a result of market impact. In the scientific field, biogenic amines have the potential to be applied as indicators of food spoilage. Biogenic amines are essential at low concentrations for metabolic and physiological functions in animals, plants, and microorganisms, but at high concentrations can induce adverse reactions in susceptible individuals. Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Different microorganisms present in wine can synthesise biogenic amines from their respective amino acid precursors, at any stage of wine production, ageing or storage. Therefore, their presence in wines can serve as an indicator of spoilage and authenticity [164,165]. Biogenic amines associated with grape wine are putrescine, histamine, tyramine and cadaverine, followed by phenylethylamine, spermidine, spermine, agmatine and tryptamine [162].…”
Section: Biogenic Aminesmentioning
confidence: 99%
“…Different microorganisms present in wine can synthesise biogenic amines from their respective amino acid precursors, at any stage of wine production, ageing or storage. Therefore, their presence in wines can serve as an indicator of spoilage and authenticity [164,165]. Biogenic amines associated with grape wine are putrescine, histamine, tyramine and cadaverine, followed by phenylethylamine, spermidine, spermine, agmatine and tryptamine [162].…”
Section: Biogenic Aminesmentioning
confidence: 99%
“…As an alternative to the previous approaches based on production mitigation and degradation of the BA, other studies have focused on the removal of the BA from the final wines. The studies carried out under usual enological treatments, clarification and fining, have shown that the most effective coadjuvant was bentonite 14,15 . However, although bentonite is currently used in white winemaking for protein removal in order to avoid wine turbidity after bottling, the drawbacks of its use, related to the removal of volatile compounds, thus affecting aroma, are also well known 16,17 .…”
mentioning
confidence: 99%